Political Preferences of Muslim Generation Z in the Digital Age: A Case Study of Students at UIN SATU Tulungagung - Siti Khoirotul Ula; Binti Lailatul Masruroh (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2026)
This research analyzes the preferences of UIN Sayyid Ali Rahmatullah (UIN SATU) Tulungagung students, as representatives of Generation Z, toward political content on social media. This study aims to determine the preferences of UIN SATU Tulungagung students for political content on social media, a typology of their chosen political social media, and analyze it using agenda-setting theory to understand the influence on their political awareness. This study uses a descriptive-prescriptive qualitative approach with a case study, interviews with 90 respondents via Google Forms, FGDs with 17 informants, and analysis using agenda-setting theory. The research findings indicate that almost all students (91%) consistently access political content thru Instagram, TikTok, X, and YouTube for quick insights, engaging visuals, and diverse perspectives that are considered more credible than mainstream media. Their primary preferences include accounts like Kompas.com, Tirto.id, PinterPolitik, Malaka Project, and Mojok.co, with content characterized by informative articles, infographics/short videos, relevance to social issues such as human rights, education, government transparency, and critical/progressive narratives that encourage discussion. They categorized accounts into five typologies: (1) mainstream news (Kompas.com, CNN Indonesia) for neutral facts; (2) political literacy (PinterPolitik, Perspektif.Idn) with educational infographics; (3) activism/criticism (Malaka Project, Social Movement Institute) focusing on social justice; (4) satire/narrative (Mojok.co, Harus Mikir) combining humor and analysis; and (5) personal/institutional (Akbar Faizal, Constitutional Court) for vocal opinions or formal law. They compared the advantages/disadvantages of accounts, demonstrating high digital literacy despite 37.6% being inactive in organizations. Agenda setting by these accounts shapes opinions thru issue salience such as corruption, government policy, and public welfare, raising critical awareness without directly determining political choices—the majority of respondents (in three forms: fully/partially/not influenced) use them for reflection, multi-source analysis, and social participation. The findings confirm that Generation Z at UIN SATU has good literacy, is sensitive to civil issues, and is independent in filtering out hoaxes/polarization